2015
DOI: 10.3892/etm.2015.2818
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of segmental/lobar pattern Mycoplasma pneumoniae pneumonia: A ten-year retrospective clinical study

Abstract: plays an important role in community-acquired pneumonia. However, epidemiological and clinical studies on the segmental/lobar pattern (S/L) radiographic-pathologic subtype of pediatric pneumonia (MPP) are rare. The current study retrospectively analyzed the epidemiological and clinical characteristics of pediatric MPP patients. A total of 1,933 children with MPP received treatment at a single hospital between 2000 and 2009, of which 684 (35.4%) were diagnosed with S/L-MPP. The annual incidence of S/L-MPP in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 32 publications
10
30
1
Order By: Relevance
“…Youn et al [8] also reported longer fever duration in patients with a lobar pneumonia pattern, as well as a noticeable increase in CRP. In addition, Gao et al [10] also reported longer fever duration, elevated levels of WBC and CRP, with associated extrapulmonary symptoms, and longer hospitalization in the lobar pneumonia group. This study showed a similar trend of longer fever duration and higher platelets, CRP, and ESR in the lobar pneumonia group.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Youn et al [8] also reported longer fever duration in patients with a lobar pneumonia pattern, as well as a noticeable increase in CRP. In addition, Gao et al [10] also reported longer fever duration, elevated levels of WBC and CRP, with associated extrapulmonary symptoms, and longer hospitalization in the lobar pneumonia group. This study showed a similar trend of longer fever duration and higher platelets, CRP, and ESR in the lobar pneumonia group.…”
Section: Discussionmentioning
confidence: 94%
“…Recently published studies [8,[10][11][12][13][14] have shown an increasing lobar pneumonia pattern. This study also confirmed the lobar pneumonia pattern in about a quarter of all MP patients, also reporting on the consolidation [10][11][12][13]16] in both lower lobes as the most common location.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations